Disentangling the water, food and energy nexus in agriculture: a policy option for India [Abstract only] - Amarasinghe, Upali A. (2014)
In India, the nexus between water, food and energy has reached a tipping point. The country can no longer underestimate the crises or delay addressing the issues emanating from the nexus, which already constrain sustainable economic growth in many regions. This paper assesses the trends and turning points of groundwater irrigation, agricultural production and energy consumption in the state of Andhra Pradesh (AP), India, which exemplifies the dire situation that prevails elsewhere in the country. It also shows that the state can reduce agricultural electricity consumption and still achieve a Pareto optimal solution for all stakeholders: farmers, utility companies, the government and, most importantly, the environment. AP has an important place in economic, agricultural land- and water-scape in India. In 2011, the total population of India was 1.2 billion, of which AP accounted for 84 million people. Among the 32 major states in India, AP has the fifth largest population, fourth largest geographical area, second largest economy and 5 million hectares of net irrigated area (NIA), which is 9% of the total NIA of the country. The state has 23 administrative districts in three agro-climatic zones: Telangana, Rayalaseema and Coastal Andhra. Three distinct growth periods depict groundwater irrigation development during the last four decades. Dug wells, along with canals, were the main sources of irrigated area expansion in the 1970s and 1980s. A decline in the number of dug wells and the rapidly increasing number of tube wells were the main features of irrigation development trends in the 1990s. Post-2000 trends show a significant slowdown in the expansion of even the tube well irrigated area. Yet, groundwater depletion is an issue in many regions. Groundwater contributes to 69%, 67% and 23% of NIA in the Telangana, Rayalaseema and Coastal Andhra regions, respectively, and to 48% of the net sown area in AP. In some regions, the consumptive water use (CWU) (evapotranspiration) of crop production alone is a significant part of natural groundwater recharge. With depletion from other sectors, groundwater CWU in many locations are at or above the thresholds of natural groundwater recharge. Electricity consumption increased rapidly with groundwater use. The share of electric pumps in the state increased from 64% to 94% between 1991 and 2008. As a result, agricultural electricity consumption increased by 138% between 1991 and 2008, compared to a 57% growth in NIA using groundwater. Electricity supply is free to farmers, but a high cost has to be borne by the governments. Utility companies estimate the cost of agricultural electricity supply at a flat rate of about USD 0.08/kWh. The government transfers the estimated subsidy to the utility companies to mitigate their losses. The estimated farm power subsidy at the national level is more than USD 6 billion, which is more than the expenditure for health and education in some states. Econometric analyses of district-level data between 1999 and 2008 show that, every 1% growth in groundwater CWU has contributed to a 0.82% increase in agricultural electricity consumption and only a 0.12% gross value of crop output. Thus, a 1% reduction in agricultural electricity consumption will reduce 1.14% of groundwater CWU and will, in turn, reduce 0.14% of the gross value of output. At present, the marginal loss of gross value of output due to a reduction in electricity consumption is far less than the increase in subsidy for that amount of electricity consumed. In many districts, due to high production costs, marginal profits are much less than the subsidy that the government has to payout. Thus, the direct transfer of the electricity subsidy to farmers for reducing electricity consumption is a financially attractive option, rather than the value generated in agricultural production at present. Such a solution can generate even higher environmental and socioeconomic benefits to all stakeholders. It will maintain, at least, the present level of benefits to farmers - the most important stakeholder in the nexus. Power utility companies can reduce losses by selling power to other sectors at a higher incremental rate. The state government can reduce the agricultural power subsidy. Domestic and industrial sectors can increase their productivity and output, for which inadequate power supply is a severe constraint at present. The environment will benefit by reduced groundwater depletion, which contributes to the drying of wetlands and streams, and water quality issues, at present. It is an incentive for farmers to increase efficiency of groundwater use and diversify cropping patterns to high-value low water-intensive crops. The utility companies will have to reduce losses in power transmission and distribution, which, at present, is conveniently included in the subsidy estimation